THE EFFECT OF WORK COMMUNICATION AND TEAMWORK ON EMPLOYEE PERFORMANCE AT THE BONTONOMPO 1 HEALTH CENTER OF SOUTH BONTONOMPO SUB-DISTRICT - Nurwinda; Chalid Imran Musa; Muh. Ichwan Musa; Zainal Ruma; Tenri Sayu Puspitaningsih Dipoatmodjo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study aims to analyze the effect of communication and teamwork on employee performance at Bontonompo 1 Health Center, located in South Bontonompo District. Quantitative data was utilized for the research, with a sample size of 45 individuals. The study explored the relationship between work communication, teamwork, and employee performance to assess their combined impact on the organization's effectiveness. The findings indicated that both work communication and teamwork had a significantly positive influence on employee performance. The f-statistic value of 34.965 surpassed the f-table value of 3.23, with a remarkably low significance value of 0.000. This statistical result affirms the robust and meaningful impact of effective work communication and collaborative teamwork on enhancing employee performance. In a well-functioning workplace, clear and open communication channels foster seamless exchanges of ideas, feedback, and information among employees, supervisors, and teams. Moreover, the study highlights the importance of teamwork in achieving organizational objectives. When employees work together as a unified team, they share responsibilities, support each other, and pool their diverse skills and expertise, leading to higher levels of productivity and efficiency. Teamwork encourages collective creativity and problem-solving, which are invaluable assets in a dynamic and demanding work environment. The results of this study reinforce the idea that effective communication and teamwork are not only individually valuable but also interrelated and complementary factors in driving employee performance. Organizations that prioritize nurturing a culture of open communication and teamwork are more likely to witness improved employee satisfaction and engagement, ultimately contributing to enhanced overall organizational performance.